The effect of rapid privatisation on mortality in mono-industrial towns in post-Soviet Russia: a retrospective cohort study - Dr Aytalina Azarova, PhD; Darja Irdam, PhD; Alexi Gugushvili, PhD; Mihaly Fazekas, PhD; Gábor Scheiring, MA; Pia Horvat, PhD; Denes Stefler, PhD; Prof Irina Kolesnikova, PhD; Prof Vladimir Popov, PhD; Prof Ivan Szelenyi, PhD; Prof David Stuckler, PhD; Prof Michael Marmot, PhD; et al. (Elsevier, 2017)
Background: Population-level data suggest that economic disruptions in the early 1990s increased working-age male mortality in post-Soviet countries. This study uses individual-level data, using an indirect estimation method, to test the hypothesis that fast privatisation increased mortality in Russia. Methods: In this retrospective cohort study, we surveyed surviving relatives of individuals who lived through the post-communist transition to retrieve demographic and socioeconomic characteristics of their parents, siblings, and male partners. The survey was done within the framework of the European Research Council (ERC) project PrivMort (The Impact of Privatization on the Mortality Crisis in Eastern Europe). We surveyed relatives in 20 mono-industrial towns in the European part of Russia (ie, the landmass to the west of the Urals). We compared ten fast-privatised and ten slow-privatised towns selected using propensity score matching. In the selected towns, population surveys were done in which respondents provided information about vital status, sociodemographic and socioeconomic characteristics and health-related behaviours of their parents, two eldest siblings (if eligible), and first husbands or long-term partners. We calculated indirect age-standardised mortality rates in fast and slow privatised towns and then, in multivariate analyses, calculated Poisson proportional incidence rate ratios to estimate the effect of rapid privatisation on all-cause mortality risk. Findings: Between November, 2014, and March, 2015, 21 494 households were identified in 20 towns. Overall, 13 932 valid interviews were done (with information collected for 38 339 relatives [21 634 men and 16 705 women]). Fast privatisation was strongly associated with higher working-age male mortality rates both between 1992 and 1998 (age-standardised mortality ratio in men aged 20-69 years in fast vs slow privatised towns: 1·13, SMR 0·83, 95% CI 0·77-0·88 vs 0·73, 0·69-0·77, respectively) and from 1999 to 2006 (1·15, 0·91, 0·86-0·97 vs 0·79, 0·75-0·84). After adjusting for age, marital status, material deprivation history, smoking, drinking and socioeconomic status, working-age men in fast-privatised towns experienced 13% higher mortality than in slow-privatised towns (95% CI 1-26). Interpretation: The rapid pace of privatisation was a significant factor in the marked increase in working-age male mortality in post-Soviet Russia. By providing compelling evidence in support of the health benefits of a slower pace of privatisation, this study can assist policy makers in making informed decisions about the speed and scope of government interventions. Funding: The European Research Council.